Intraspecific Morphometric Variation in a New Species of Ceratomyxa Thélohan 1892 (Cnidaria) from the South Atlantic Ocean: An Ecomorphological Study Using Geometric Morphometrics - Cantatore, Delfina María Paula (2025)
A new species of Ceratomyxa (Ceratomyxidae, Myxosporea) was found infectingthe gall bladder of the Argentine croaker Umbrina canosai Berg 1895 (Sciaenidae, Perciformes) from the Argentine sea. Using an integrative taxonomic approach that combinesmorphological, bioecological, and molecular analyses, we provide evidence that clearlydifferentiates this species from known taxa and formally describe Ceratomyxa fialai as a newspecies. This study is the first to apply landmark-based geometric morphometrics (GM) inmyxozoan research, providing a detailed analysis of conspecific morphometric variation ofceratomyxid myxospores, examining their natural variation within and among differentceratomyxids infecting the gall bladder of U. canosai. Using GM analyses, we successfullycapture and quantify phenotypic variation at the organismal level. Our results suggestthat myxospore shape variation may be driven by both developmental noise and phenotypic plasticity. The work highlights the utility of GM in advancing the understandingof myxozoan morphology and its evolutionary implications and emphasizes the need forfurther research on myxospore shape evolution and its ecological and adaptive significancein natural populations.